Motor skills of children with autism spectrum disorder - Gabriele Radünz Krüger; Jennifer Rodrigues Silveira; Alexandre Carriconde Marques (Universidade Federal de Santa Catarina, 2019)
The objective of this study is to describe variables of life habits associated with motor skills of children with autism spectrum disorder aged 8-10 years living in the city of Pelotas / RS. A questionnaire about lifestyle was applied and the Test of Gross Motor Development-2 (TGMD-2) was applied to assess motor skills. Independent T-test, ANOVA and Wilcoxon test were used to compare means. The study consisted of 49 individuals (42 males). The results indicate that the higher the level of ASD, the better the motor skills. Children making use of medications have greater deficits in motor skills. Higher scores on motor skills are associated with greater participation in physical education classes. Motor skills are strongly associated with independence in activities of the daily living, food, personal hygiene, dressing and bathing. The importance of the creation of PA programs aiming at improving the motor skills of this population was highlighted.